XMAP: Five-Point Interpolating Map. (January 2022) - Rossignac, Jarek
Abstract: Xmap takes the unit square to a subset of a doubly curved surface. It interpolates five control-points, which are the images of the four corners and of the center of that square. Interactive tweaks of control-points produce unsurprising changes in the map. The Xmap is an extension of the BeCOTS map. When the control-points are coplanar, it is an exact generalization of the COTS map. We conjecture that Xmaps may prove useful for designing aesthetically pleasing 3D structures.